(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
اقترن النظم في أذهان الدارسين بعبد القاهر الجرحاني لأنه استطاع بفكره الخلاق أن يستفيد من جهود السابقين عليه حيث نجد قبله تراثا فكريا ولغويا كبيرا تمكن أن يشكل من نظرية تفسر من خلالها العلاقات اللغوية في السياق وهي نظرية النظم. ويمكن للباحث أن يرى في الجهود التي سبقت عبد القاهر اتجاهين مهمين كان لهما أثر كبير في تشكيل هذه النظرية عند عبد القاهر هما: 1- الاتجاه النحوي: وقد قدم النحاة جهودا عظيمة في هذا المجال وتركوا آثارا فاعلة في إبراز جوهر هذه النظرية بدءا بسيبويه ومرورا بمن جاء بعده حتى القرن الرابع الهجري حيث ارتدت الدراسة اللغوية ثوبا زاهيا بهيا يتمثل بما وجدناه عند الفارس وتلميذه ابن جني وعبد القاهر نفسه كان من كبار النحاة. وقد ساهم في إرساء القواعد اللغوية ليصل إلى تأسيس هذه النظرية كنظرية للفكر اللغوي العربي. 2- الاتجاه الذي يبحث في وجوه إعجاز القرآن: والإعجاز قضية كبرى اشتغل عليها النقاد العرب كالماني النحوي والخطابي والقاضي عبد الجبار والباقلاني وغيرهم. وما يلاحظ هنا أيضا أن أكثر هؤلاء كان يعتمد في جانب من جوانب الإعجاز على الفكر النحوي (معاني النحو) وعبد القاهر كان واحدا من هؤلاء حيث كانت له (رسالة في إعجاز القرآن) ضمن ثلاث رسائل حتى وضع كتابه (دلائل الإعجاز) ليقصر فيه الإعجاز على النظم والنظم حقيقة هو جوهر التركيب اللغوي وهو يعرفه بقوله: (ليس النظم إلا أن تضع كلامك الوضع الذي يقتضيه علم النحو). وما سبق يعني أن عبد القاهر سيبني نظريته في النظم على أساس من الفكر النحوي فقد وجد بناء لغويا شامخا وتراثا فكريا عظيما فما كان منه إلا أن قام بلم شتات الأفكار والملاحظات المتناثرة في تراث سابقيه ليشكل من ذلك نظرية النظم فأضاف إلى ملامح عبقريته الخلاقة وألوان ذوقه اللطيف وحسه المرهف فتخرج النظرية في النهاية نظرية الفكر اللغوي العربي. Verse composition was coupled into scholars mind with Abed Al-Kaher Al-Gergani for he was able to get benefit from efforts of his antecedents through the theme of creator where we could find out a great linguistic and intellectual heritage of which he had an ability to form a theory to interpret linguistic relationships in this context, that is theory of verse composition. A researcher can discover in efforts that come prior to Abed Al-Kaher, two important directions having a huge impact on establishing Abed AlKaher’s theory, they are: 1. Syntax direction: Grammarians made great efforts in this walk leaving reactive traces in showing the essence of this theory from Sibawayh throughout those who came later until the Hijri 4t" Century where linguistic study had worn a bright colorful garment represented by what we found with Al-Farisee and his scholar Ibn-Jinni, and Abed AlKaher himself was one of the greatest grammarians where he participated in establishing linguistic grammars so as to reach foundation of this theory as a theory of Arabic linguistic thought. 2. Direction seeking for aspects of Koran miracle: Miracle is a great question on which Arab criticizers have been working as Al-Rammani the grammarian. Al-Khitabi, Abed Al-Gabar the judge, and Al-Baklani and others. What noteworthy here is that most of them had relied on one of sides of miracle on grammatical thought (grammar semantics) and Abed Al-Kaher was one of them, where he had a "message in Koran miracle" within three messages, until he put his book "Miracle Evidences" in which he briefed miracle into verse composition which is, in fact, the essence of linguistic structure as he defined it "verse composition is that to put your speech in a position required by grammar". What mentioned above means that Abed Al-Kaher would build his theory of verse composition on basis of grammarian thought where he found out a lofty linguistic structure and a great intellectual heritage, so he collected the scattered ideas and dispersed remarks of his antecedent’s heritage to form theory of verse composition out of that where he added the features of his creative genius, colors of his gentle taste and his sensitive feeling in order to emerge of the theory of Arab linguistic thought at the end.